2008
DOI: 10.1177/1533317508325094
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Vitamin/Nutriceutical Formulation for Moderate-stage to Later-stage Alzheimer's disease: A Placebo-controlled Pilot Study

Abstract: Recent studies demonstrated efficacy of a vitamin/ nutriceutical formulation (folate, vitamin B12, alpha-tocopherol, S-adenosyl methionine, N-acetyl cysteine, and acetyl-L-carnitine) for mild to moderate Alzheimer's disease. Herein, we tested the efficacy of this formulation in a small cohort of 12 institutionalized patients diagnosed with moderate-stage to later-stage Alzheimer's disease. Participants were randomly separated into treatment of placebo groups. Participants receiving the formulation demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 60 publications
(75 reference statements)
4
107
0
Order By: Relevance
“…Trials are underway among participants with early [85] and late-stage AD [86]. In addition, multidomain interventions encompassing nutritional, physical and cognitive training may offer a potential synergistic effect in preventing cognitive decline in susceptible populations [87].…”
Section: Discussionmentioning
confidence: 99%
“…Trials are underway among participants with early [85] and late-stage AD [86]. In addition, multidomain interventions encompassing nutritional, physical and cognitive training may offer a potential synergistic effect in preventing cognitive decline in susceptible populations [87].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, communitydwelling subjects with early stage Alzheimer's disease improved in a one-year study [38]. In another study, vitamins with nutriceuticals were used to treat moderate and late stage Alzheimer's disease over nine months [39]. A third study used the herbal, panax ginseng, in a double blind study of 97 subjects to successfully treat Alzheimer's patients [40].…”
Section: Memory and Antioxidantsmentioning
confidence: 99%
“…Some studies have shown that combinations of antioxidants can be beneficial for pathologies associated with increased oxidative stress (55) and that such a strategy might be advantageous over higher doses of single antioxidants for treating mitochondriopathies (62,63), reproducing what it is already present in nature; that is, a combination of antioxidant systems rather than a single one. In particular, it has been recently demonstrated that several combinations of antioxidants {[LA, NAC and vitamin E (4)], [LA and NAC (41)], or [LA and acetyl-L-carnitine (1, 57)]} are able to prevent oxidative damage and improve mitochondrial ultrastructural decay or dysfunction in Alzheimer disease mouse models (57), and even in some clinical studies (13,51). Further, since LA is an essential cofactor of PDHC and KGDHC, its supplementation could protect and increase the enzymatic activity of KGDHC (2), and, therefore, help bring about an increase in NADH and ATP production.…”
mentioning
confidence: 99%